Supply chain risk management in crisis situations - Daniel Müller; Ayman Nagi; Meike Schröder (Changing Tides: The New Role of Resilience and Sustainability in Logistics and Supply Chain Management – Innovative Approaches for the Shift to a New Era. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 33, 2022)
Purpose: The aim of the paper is to develop a concept for implementing supply chain risk management (SCRM) in crisis situations based on recommendations for action. Methodology: The paper utilizes a mixed-method approach based on a systematic literature review and an interview study to analyze the state of research and practice in order to extract the recommendations for action. Findings: The insights gained from the analysis of existing approaches and the findings from the expert interviews are incorporated into the development of the concept. This includes general recommendations for implementing a SCRM as well as specific measures for preparing for and managing crisis situations. Originality: The concept is intended to support companies in implementing a suitable SCRM system that supports a systematic improvement in the resilience of companies with regard to risks and crises and forms the bases for effective crisis management.
urn:nbn:de:gbv:830-882.0200947; hdl:10419/267179; https://econpapers.repec.org/RePEc:zbw:hiclpr:33
Keywords: 650; Supply Chain Risk Management; Security Management